Pengaruh Debt to Equiy Ratio, Return on Asset, Firm Size dan Kepemilikan Saham Publik terhadap Konservatisme Akuntansi (Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2014 – 2023) - Noviyanti, Ria; Berliani, Kartika (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Finding out how accounting conservatism is affected by the debt to equity ratio, return on assets, firm size, and public share ownership in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2014–2023 period is the aim of this study. Quantitative research methodology with a descriptive and verificative approach is employed. The financial statements (annual reports) of manufacturing firms in the Food and Beverage Subsector listed on the Indonesia Stock Exchange between 2014 and 2023 comprise the data used. Using the t-test, the research findings indicate that public share ownership and firm size have a negative impact on accounting conservatism, although return on assets and debt to equity ratio have no influence. The Debt to Equity Ratio, Return on Asset, Firm Size, and Public Share Ownership all significantly impact Accounting Conservatism, according to the simultaneous test results.